Cellulitis in older people over 75 years – are there differences?. (January 2020) - Kumar, Manoj; Jong Ngian, Vincent Jiu; Yeong, Clarence; Keighley, Caitlin; Van Nguyen, Huong; Ong, Bin Soo
Abstract: Aim: To examine differences in risk factors, clinical features and outcomes of cellulitis between those 75 + years and those <75 years admitted to a metropolitan hospital. Methods: A prospective study of patients with limb cellulitis requiring intravenous antibiotics conducted at Bankstown-Lidcombe Hospital, Australia from June 2014 to April 2015. Results: Thirty one patients were 75 + years and 69 less than 75 years. A greater proportion of older patients resided in nursing home (25.8% vs 2.9% respectively, p = 0.001) and mobilized with walking aid(s) (58.1% vs 11.6% respectively, p < 0.001). Significantly more older patients had documented hypertension (45.2% vs 23.2% respectively p = 0.035), atrial fibrillation (33.5% vs 5.8% respectively, p < 0.001), dementia (22.6% vs 1.4% respectively, p = 0.001) and malignancy (16.1% vs 1.4% respectively, p = 0.010). The clinical presentation of cellulitis and cellulitis severity (Eron classification) did not significantly differ in both groups; however older patients were more likely to have dependent edema (OR 4.0, 95%CI 1.3–12.6, p = 0.018) and less likely to be obese (OR 0.3, 95%CI 0.1–0.8, p = 0.012) or had a past history of cellulitis (OR 0.3, 95%CI 0.1–1.0, p = 0.044) on presentation. Despite the age difference, there were no major differences in intravenous antibiotic choice, hospital length of stay, and hospital readmission rates in both groups. Older patients however, were more likely to experience complications such as falls and/or decreased mobility (38.7% vs 15.9% respectively, p = 0.020) during the cellulitis episode. Conclusion: There are minor differences in the risk factors and clinical features of cellulitis in older patients as compared to the young. Outcomes are similar except for a higher incidence of hospital related complications. Highlights: To examine the differences in outcomes of cellulitis in hospitalized patients who are 75 + years and those <75 years. A prospective study of patients with limb cellulitis requiring intravenous antibiotics conducted at Bankstown Hospital. Older people had similar outcomes to younger patients after presenting to hospital with mild to moderate limb cellulitis.